Learning English in Primary School Activity Plan: A Study of Teachers with a Non-English Background - Yusrina, Aletta Wening; Setyaningsih, Endang; Putra, Kristian Adi (Universitas Pendidikan Mandalika, 2025)
English language learning in primary schools still needs more attention, especially regarding teacher training in designing effective lesson plans. Many teachers do not have an English language education background and have never received training in designing English language learning activities, so they have difficulty developing materials that meet students' needs. This study aims to determine how primary school teachers develop and implement English language learning activities in the classroom. This study used a qualitative approach with data collection through in-depth interviews, observations, and document analysis. The research subjects were two primary school teachers with a classroom teacher education background and teaching experience of 6 and 11 years respectively. The results showed that the teachers developed learning by watching learning videos and consulting with more experienced colleagues as a form of initiative and creativity in dealing with limited competencies and resources. They also face challenges in adapting methods to different student learning styles and managing limited learning time. Observations show that although the implementation of lesson plans is going according to plan, there are still problems with student participation, understanding of the material, and the effectiveness of activities, so adjustments to teaching strategies are needed. This study highlights the importance of sustained and equitable professional development so that all teachers, including those without an English education background, are able to teach adaptively and effectively in diverse classrooms.